Outcome of neonatal jaundice in term neonates with ABO incompatibility at tertiary level center - Thakur, Amit Kumar; Ansari, Mohammad Ashfaque; Mishra, Atindra; Jha, Saroj Kumar (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal jaundice is extremely common as almost every new-born develops an unconjugated serum bilirubin level of more than 1.8 mg/dl during the first seven days of life. ABO incompatibility is associated in about 20% of all pregnancies but manifestations of ABO haemolytic disease of new-born occurs in <10% of these cases. True incidence of ABO incompatibility, particularly in developing countries like Nepal, is not understood sufficiently. Furthermore, the confirmation of severe ABO incompatibility cannot be made accurately using only a single test. Hence, this study was done to know the outcome of jaundice in ABO incompatibility patients. Methods: This was a descriptive cross-sectional study done at Department of Paediatrics, between August 2018 to July 2019. All term neonates born to ‘O’ positive mother, with blood group A or B positive, and fulfilling the selection criteria were included in the study. Sample size was calculated to be 114 with confidence level at 95% and prevalence of ABO haemolytic disease as 11.4% with margin of error 5%. Results: Severe ABO incompatibility as evident by presence of jaundice within 24 hours of life, a positive result on direct coomb’s test and haemolytic picture on peripheral blood smear was observed in 12% of the total enrolled 200 neonates. Modalities of treatment showed significant relation with severe ABO incompatibility indicating increased need for double volume exchange transfusion in neonates with severe ABO incompatibility. Conclusions: Phototherapy was found to be effective in the management of most of the cases of neonatal jaundice in term ABO incompatible neonates but some cases, requiring exchange transfusion can occur, mostly in presence of positive result on direct Coomb’s test.